Physical activity and sedentary lifestyle towards teenagers’ overweight/obesity status - Bhargava, Madhavi; R, Pracheth (International Journal Of Community Medicine And Public Health, 2017)
We read the article titled, “physical activity and sedentary lifestyle towards teenagers’ overweight/obesity status” with interest.1 The authors have done a commendable job in highlighting the role of physical activity in the teenagers towards increasing overweight and obesity. Their effort is admirable. The study provides good insights into present day problems of increased technology dependence and reducing outdoor physical activity like walking and cycling. However, the following issues need to be addressed not just in the article, but also for wider dissemination and understanding.